Integration of palliative care into phase I oncology trials: A qualitative interview study with patients, informal caregivers, and healthcare providers - Frederick Daenen; Anne van Driessche; Anne-Lore Scherrens; Annelies Janssens; Sylvie Rottey; Lore Decoster; Peter A. J. Stevens; Koen Pardon; Aline De Vleminck; Kim Beernaert (PLoS ONE, 2026)
Background Patients with advanced cancer participating in phase I clinical trials often face limited survival while experiencing significant symptom burden. Despite evidence supporting early palliative care integration alongside active cancer treatment to improve quality of life, the role of palliative care in phase I trials remains unclear. Objective To explore perspectives of patients, informal caregivers, and healthcare providers on quality of life and palliative care in phase I oncology trials, including perceived benefits, barriers, and integration strategies. Methods We conducted a multi-perspective qualitative interview study across three Belgian university hospitals from September 2022 to July 2024, using convenience and snowball sampling. The semi-structured interviews were analyzed using qualitative content analysis. Ethical approval was gained from the relevant institutions. Results Participants included sixteen patients, five informal caregivers, twelve phase I staff, six oncologists, five palliative care specialists, and four general practitioners. Patients generally reported positive experiences with trial participation, often viewing it as a final opportunity that provided hope and structure. However, quality of life support was inconsistently addressed and largely reactive. While patients reported feeling supported, non-trial providers and caregivers noted limited person-centered care. No systematic approach for introducing palliative care was in place. Palliative care was rarely discussed, hindered by misconceptions such as equating palliative care with terminal care, reluctance from patients and clinicians, and lack of communication between providers. Participants suggested the introduction of routine yet flexible palliative care conversations, as well as improved communication between providers, as strategies towards integration. Conclusion Despite recognized care needs, palliative care is not systematically integrated in phase I oncological trials. Quality of life remains a secondary concern. Integrating palliative care in a structured yet flexible manner could support more holistic, patient-centered care. These findings underscore the need to normalize palliative care as a complementary component of phase I oncological trials.